2000
DOI: 10.3758/bf03212127
|View full text |Cite
|
Sign up to set email alerts
|

On asymmetries in cross-modal spatial attention orienting

Abstract: In a previous study, Ward (1994) reported that spatially uninformative visual cues orient auditory attention but that spatially uninfonnative auditory cues fail to orient visual attention. This cross-modal asymmetry is consistent with other intersensory perceptual phenomena that are dominated by the visual modality (e.g., ventriloquism). However, Spence and Driver (1997) found exactly the opposite asymmetry under different experimental conditions and with a different task. In spite of the several differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
88
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 21 publications
10
88
3
Order By: Relevance
“…The relationship between audition and vision in exogenous spatial attention is asymmetric-that is, exogenous auditory cues influence visual perception (Spence & Driver, 1994) but visual cues do not seem to affect auditory perception (Driver & Spence, 1998). These results are challenged by those of Ward (1994) and Ward, McDonald, and Lin (2000) who reported exactly the opposite asymmetry, albeit in different experimental setup with rather complex cueing and a nonspatial go/no-go task. The nonspatial response task was subsequently identified as the important difference between those studies (Spence, McDonald & Driver, 2004;Koelewijn, Bronkhorst & Theeuwes, 2010).…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The relationship between audition and vision in exogenous spatial attention is asymmetric-that is, exogenous auditory cues influence visual perception (Spence & Driver, 1994) but visual cues do not seem to affect auditory perception (Driver & Spence, 1998). These results are challenged by those of Ward (1994) and Ward, McDonald, and Lin (2000) who reported exactly the opposite asymmetry, albeit in different experimental setup with rather complex cueing and a nonspatial go/no-go task. The nonspatial response task was subsequently identified as the important difference between those studies (Spence, McDonald & Driver, 2004;Koelewijn, Bronkhorst & Theeuwes, 2010).…”
Section: Introductioncontrasting
confidence: 54%
“…While many studies have reported cross-modal cueing effects of visual cues on auditory perception in endogenous cueing experiments (Farah et al 1989;Spence & Driver, 1996;Eimer & Schröger 1998), the results of studies involving exogenous cues are rather inconclusive (Buchtel & Butter, 1988;Spence & Driver, 1997;Ward et al 2000). In three experiments, we employed both types of cues in an audiovisual redundant signals task.…”
Section: Discussionmentioning
confidence: 99%
“…The front loudspeaker was also the location at which participants were to maintain the narrow beam of a headlight they were wearing-that is, the location that they were attending while trying to identify the syllables. Finally, when visual information directs spatial attention to a certain location, reactions to auditory targets occurring at that location are faster than reactions to targets occurring at other locations (Ward, McDonald, & Lin, 2000). In sum, these findings converge with the evidence reported in the present article that the orienting of spatial attention in one modality (the visual modality in the present case) affects attention in another modality (the auditory modality in the present case).…”
Section: Discussionsupporting
confidence: 75%
“…Results from this line of research are also not conclusive. For instance, Ward (1994) and Ward, McDonald, and Lin (2000) reported that visual cues affect both visual and auditory localization, but auditory cues affect only auditory localization. Ward concluded that these results were not consistent with the hypothesis of modality-specific attentional mechanisms and suggested that the visual spatial attention system dominates over the auditory spatial attention system.…”
mentioning
confidence: 99%